EBITDA as an Indicator of Operating Cash Flows - Empirical Verification - Czajor , Przemysław; Michalak , Marcin (Studia Oeconomica Posnaniensia, 2018)
The article is an attempt to verify, if EBITDA or EBITDA adjusted with changes of working capital is a good indicator of operating cash flows. An Empirical study was performed on a sample of 46 listed companies (5 industry sectors). The study revealed that both metrics (EBITDA and the adjusted EBITDA) are not very close to real operating cash flows and one should be careful when using them instead of real cash flows. On the other hand, the differences between those metrics and operating cash flows are lower for positive cash flows.